Acromegaly with the sleep apnea syndrome. - Ferreira, A M (1997)
The authors present the clinical of a male patient aged 45 years whose main complaints were loud snoring and excessive daytime sleepiness. Polysomnographic study revealed a sleep obstructive apnea syndrome with an apnea/hypopnea index of 86.5. After being treated with nasal continuous positive air pressure, (12 cm H2O), the apneas ended and sleep architecture was corrected. Physical examination also indicated the presence of an acromegaly, and therefore, the patient was subjected to endocrinological and cerebral imagiological studies; the diagnosis confirmed it as a predisposing factor to the sleep breathing disorder. A brief literature review about the incidence of sleep apnea syndrome in acromegaly is also made; the authors conclude that there is still the need for a systematic screening of sleep breathing disorders in acromegalic patients in order to optimise the treatment and prognosis of this disorders.